The role of strategic Management in Micro, Small, and Medium Enterprises (MSMEs): A literature study - Ni Nyoman Padang Cakra Binaraesa; Ikayanti Ikayanti; Nuryadi Nuryadi (Privietlab, 2026)
Micro Small and Medium Enterprises (MSMEs) play a very important role in the economic development of a country, which also contributes significantly to global economic growth. Market competition is getting tighter and is becoming a problem for MSMEs; therefore, strategic management is needed as the main reference source to support the success of MSME businesses. This study aims to determine and examine the role of strategic management in MSMEs, especially in MSME business performance, MSME business development, the competitive ability of MSME businesses, and the sustainability and success of MSME businesses. This research presents a review of the literature through a literature study approach with qualitative descriptive analysis. This study reviewed 50 articles obtained and 33 selected scientific articles on the role of strategic management in MSMEs, which is linked to MSMEs performance, competitive ability, development, and the sustainability and success of MSME businesses, with a focus on the period 2008 to 2022. The results of this study show that the implementation of strategic management is very important in the MSME business sector. Strategic management can improve MSME business performance, increase the competitive ability of MSMEs, and make MSME businesses more developed and successful.